The administration of a university with particular reference to the University of Cape Town - deVries, Peter (Department of Political Studies, 2024)
[pg 168 missing] There have been schools of learning in many parts of the world dating back to ancient times: in the fifth century before the birth of Christ the first University that we have knowledge of flourished as Nisibis in Asia Minor; in Ancient Greece Plato also instructed his little group of pupils in the grove near Athens named after the god of forests, Academus; but it was not from either of these or any preceeding institutions of learning that the universities, as we know them today, evolved. Our universities took their form and traditions from institutions of the Middle Ages. The medieval institutions for higher learning evolved from schools which were attached to the Medieval cathedrals in centres known as stadia. Famous schools of this type were to be found at Salerna, Bologna and Paris in 1050. The early stadia were not created but grew as the natural expression of the spiritual, intellectual and social energies of the age - fundamentally they were meeting places of students and masters drawn together by a common desire for learning.